Technical Accuracy and Efficiency of Magnetic Resonance Imaging in Evaluation of Female Adnexal Pathology in Comparison with Ultrasound - Aseel Kamal Mahmood; Haider Qasim Hamood; Khaleel Akeash Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The masses or cysts of the ovary, masses of the fallopian tube, pathology of the broadligament, and cysts of the para tubal are all referred to as adnexal masses. The first-line imaging modalityis ultrasound. MR imaging has played and continues to be of high importance in treating adnexal diseasepatients.Purpose: To equate the diagnostic accuracy regarding ultrasound and Magnetic Resonance Imaging (MRI)in females with adnexal pathology.Patients and method: The research was conducted in Baghdad medical city/radiology institute. There were60 women in this study. If ultrasound is associated with adnexal pathology, all patients have been subjectedto MRI and ultrasound examination. The imaging was done with a (Mindray, Dc-80A) ultrasound machine.1.5 Tesla was used for the MRI (Magnetom Avanto, Siemens).Results: In an MRI study of 60 patients, the right-side lesions were found in 25 (46%), the left side lesionseen in 24 (44%), and bilateral in 6 (11%). In an MRI, 37 (61%) of the patients were cystic, while 18 (30%)were complex mass lesions. Regarding diagnosis of malignant lesions with MRI, the sensitivity, precision,and accuracy were all 100%, 100%, and 100%, respectively.Conclusions: For the measurement of pelvic masses, ultrasound is often used as the first imaging modality.The high contrast resolution of MRI allows for precise tissue characterization and better anatomic delineation.In the case of benign pathologies, this would undoubtedly assist in preventing needless surgeries.